Dampak Covid 19 Terhadap Sosial-Ekonomi Masyarakat Di Desa Lomaya - Sako, Siti Fadila; Ibrahim, Sulaiman; Lasoma, Arniati; Yusup, Kurniati (Madani: Jurnal Pengabdian Ilmiah, 2022)
Since declared a pandemic, the spread of Covid-19 has impacted all aspects of life, including socio-economics. Lomaya Village, which is in a position between Tapa and North Bulango, has also issued various policies to protect its people from Covid-19. In general, so many social activities in Lomaya Village after the spread of Covid-19 appear to have significantly changed socio-economic aspects. For this reason, this research was conducted to see the impact of Covid-19 on the socio-economic factors of the people in the Lomaya Village. This study used a qualitative method with the primary data source obtained from the results of observations and interviews. A literature review was used to complement the research, which was obtained from previous research. This study indicated that there were significant changes to the socio-economic activities of the people in Lomaya Village before and during the Covid-19 period.